JAMES MARSHALL-CORNWALL: Foch as Military Commander - Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
Marshal Foch will always be remembered along with Joffre, Petain, Waygand, Castelnau and the other French commanders who on several occasions helped to save their country from catastrophe during the First World War. In this book General Marshall-Cornwall considers the contribution of Foch to France's war effort and to ultimate Allied victory. As befits a volume in the 'Military Commanders' series, the bulk of the account (thirteen chapters out of twenty-one) is devoted to the period of hostilities. The first eight chapters cover Foch's early years and the development of his military throught and philosophy, and proceed to an evaluation of the European political situation in the years before 1914, including the evolution of the Entente CordiaIe.